Highlights on the First Line Treatment of Metastatic Pancreatic Cancer - Gunturu, Krishna S; Jarboe, Jamie; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
Pancreatic cancer is the fourth leading cause of cancer deaths in men and women. The estimated deaths from pancreatic cancer in 2012 in the United States are 37,390, and the five-year survival for all patients with pancreatic adenocarcinoma is less than 5%. Majority of patients present with incurable metastatic pancreatic cancer. The 2012 American Society of Oncology (ASCO) Annual Meeting offered new insights into metastatic pancreatic cancer and we discuss Abstracts #4018, #4019, #4022, #4042, #4043, #4048, #4050 and comment on them in this paper. Image: Stained glass windows by Tommaso Juglaris at Goddard Chapel at Tufts University. Medford, MA, USA (Emily Zilm for Tufts University).